Thick Does the Trick: Genesis of Ferroelectricity in 2D GeTe-Rich (GeTe)m (Sb2 Te3 )n Lamellae - Cecchi, Stefano; Momand, Jamo; Dragoni, Daniele; Abou El Kheir, Omar; Fagiani, Federico; Kriegner, Dominik; Rinaldi, Christian; Arciprete, Fabrizio; Holý, Vaclav; Kooi, Bart J; Bernasconi, Marco; Calarco, Raffaella (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2024)
The possibility to engineer (GeTe)m (Sb2 Te3 )n phase-change materials to co-host ferroelectricity is extremely attractive. The combination of these functionalities holds great technological impact, potentially enabling the design of novel multifunctional devices. Here an experimental and theoretical study of epitaxial (GeTe)m (Sb2 Te3 )n with GeTe-rich composition is presented. These layered films feature a tunable distribution of (GeTe)m (Sb2 Te3 )1 blocks of different sizes. Breakthrough evidence of ferroelectric displacement in thick (GeTe)m (Sb2 Te3 )1 lamellae is provided. The density functional theory calculations suggest the formation of a tilted (GeTe)m slab sandwiched in GeTe-rich blocks. That is, the net ferroelectric polarization is confined almost in-plane, representing an unprecedented case between 2D and bulk ferroelectric materials. The ferroelectric behavior is confirmed by piezoresponse force microscopy and electroresistive measurements. The resilience of the quasi van der Waals character of the films, regardless of their composition, is also demonstrated. Hence, the material developed hereby gathers in a unique 2D platform the phase-change and ferroelectric switching properties, paving the way for the conception of innovative device architectures.
Keywords: molecular beam epitaxy; van der Waals; 2D ferroelectrics; density functional theory calculations; phase-change materials